KONSEP PENDIDIKAN HUMANIS PERSPEKTIF ISLAM DAN APLIKASINYA DALAM PROSES BELAJAR MENGAJAR (AL - ZARNUJI) - Herwati, Herwati; As'ari, Hasyim (LP3M UNZAH GENGGONG, 2019)
Abstract Education is an effort to learn with the help of others to achieve their goals. The purpose of humanist education or learning / gaining knowledge here is a certain condition that is used as a reference to determine the success of learning / education. In other words the purpose of education / learning in the sense of micro education is the desired condition after individuals carry out learning activities. The goal is what is declared by humans, put it as the center of attention, and for the realization of it he set his behavior. That goal is very important because it serves as the end of all activities, directs all educational activities. To achieve the above, instilling true intentions, seriousness in education, good morals and the potential that exists in humans is one of the efforts of humanist education in shaping human personality. This is certainly done through the process of intentions straightening, strong will will be able to develop all the potential possessed by humans, both physical potential and spiritual potential, (humanization). The main foundation for realizing education that is capable of producing quality human beings, must be based on values the essential, which comes from the Omniscient Essence and human values ​​(fitrah). The application of the concept of humanist education places more emphasis on educators to be able to create an atmosphere of learning that is far removed from oppression, coercion, hegemony of thought, and attitudes that are far from universal human values. The need to prioritize love and affection in interacting with students. Educators make students as partners in learning by trying to understand all the problems faced by students, there is no superiority in the teaching and learning process, so as to create a conducive learning atmosphere. Keywords: Humanist education, human characteristics, their potential, and their application in teaching and learning.